2006
DOI: 10.1007/s00428-006-0190-9
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology reporting of prostate needle biopsies. 2005 update

Abstract: This report reviews the diagnostic and prognostic importance of the pathologic findings in prostate needle biopsies. The morphological findings of the needle biopsy may be placed into one of the following five categories: prostate cancer, atypical small acinar proliferation, high-grade prostatic intraepithelial neoplasia, inflammation, and benign prostatic tissue. While the prime goal of the biopsy is to diagnose prostatic adenocarcinoma, once carcinoma is detected, further descriptive information regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 74 publications
0
10
0
1
Order By: Relevance
“…Detection of PCa was classically dependent on digital rectal examination (DRE), but owing to the development of more reliable methods of screening, especially the widespread use of serum prostatespecific antigen (PSA) testing, and imageguided needle core biopsy (e.g., transrectal ultrasound [TRUS] and, more recently, MRI), the accuracy to diagnose PCa at its earliest stages has significantly increased [2]. The advent of PSA screening was associated with an increase in PCa incidence and, probably, a decrease in cancer-related mortality, as well [3].…”
Section: Abstract: Biomarkers • Histopathology • Immunohistochemistrymentioning
confidence: 99%
“…Detection of PCa was classically dependent on digital rectal examination (DRE), but owing to the development of more reliable methods of screening, especially the widespread use of serum prostatespecific antigen (PSA) testing, and imageguided needle core biopsy (e.g., transrectal ultrasound [TRUS] and, more recently, MRI), the accuracy to diagnose PCa at its earliest stages has significantly increased [2]. The advent of PSA screening was associated with an increase in PCa incidence and, probably, a decrease in cancer-related mortality, as well [3].…”
Section: Abstract: Biomarkers • Histopathology • Immunohistochemistrymentioning
confidence: 99%
“…Nonetheless, inflammatory atrophy was found in about 40% of the adenocarcinoma cores in that study. Other studies report no significant association between prostatic inflammatory atrophy (PIA) and prostate cancer development [11,12]. PIA can be diffuse or focal, and the detection of small focal changes occurring at the peripheral zone is challenging in needle biopsies [13].…”
Section: Introductionmentioning
confidence: 99%
“…3 Diagnosis of carcinoma can also be aided by preoperative prostatic specific antigen (PSA) estimation and use of imaging studies coupled with clinical examination while biopsy remains the gold standard in confirming a carcinoma. 3 Besides reporting cancer and grading it, there are number of other features, which add to the predictive value, which may be included in the routine reporting of cancers; one such feature is estimation of MVD. Most studies have shown a positive correlation of MVD with increasing pathological grade 4,5 , while some other studies have found out that MVD is an independent predictor of cancer progression and survival.…”
Section: Discussionmentioning
confidence: 99%